Raziskovanje ovir (v polju zasebnega) za enako prisotnost žensk in moških v politiki - Selišnik, Irena (Teorija in praksa, 2012)
The text brings into focus contemporary research on equal opportunities, the entrance and activities of men and women in politics, as well as structural, system and other obstacles they face on their way to decision-making institutions. Primarily, it provides an overview of the most important, widely successful or most referenced international research in the field, together with an overview of research undertaken in Slovenia. In particular, the text addresses the research problem of how the private sphere influences public or political activity. As women are traditionally considered as being more connected to and interested in the private sphere, the text mostly deals with the problem of the obstacles women face when entering politics. Because this kind of research is missing in Slovenia, the authors (before becoming involved in studying this problem in Slovenia) examined similar research in the United States of America. On this basis and with a consideration of certain specificities of Slovenian territory, they frame methodological reflections regarding their own research project that is presented at the end of the text.
Keywords: Politics; Politika; Spol (Psihologija); Sex (Psychology); Enakost možnosti; Equal opportunity; Slovenia; Slovenija; javno; zasebno; spol; raziskovanje; ovire